An Empirical Analysis of the Effects of Mergers and Acquisitions on Commercial Bank Performance in Nigeria - Abubakar, Muktar (2015)
In recent years, merger and acquisition activities have rapidly increased among financial institutions and it has become a very important and practical corporate tool used to pursue firm growth. M&A activities not only can expand market shares but also create value for companies and shareholders.